Capital Account Liberalization and Income Inequality: A Panel Study of 28 European Countries - Muhammad Taufik Radhianshah; Akhmad Syakir Kurnia (Universitas Hayam Wuruk Perbanas, 2021)
Financial globalization has evolved from domestic policy to international scope policy. One of its form is capital liberalization which we can observe from the declining number of restrictions among countries for cross-border financial transaction, and the increasing level of capital flow between countries. Europe cross-country financial transaction has been increasing for the last three decades and this increase happened simultaneously with the increase of income inequality as measured with Gini index. This condition gives impression that there is a positive correlation between income inequality and capital account liberalization. This research aims to study whether income inequality corresponds to the increase of capital account liberalization in 28 Europe countries. Furthermore, this research seeks to understand the role of institutional quality and financial depth as threshold variables. By employing System GMM Estimator on balanced panel data, this study finds that capital account liberalization positively correlated with income inequality and institutional quality proven to be important threshold variable. These findings emphasize the urgency for policy maker to consider institutional quality before or during the implementation of capital account liberalization.